Avaliação das estratégias do Programa Nacional de Controle da Dengue e as epidemias anuais da doença no Brasil - Rodrigues, Elisângela de Azevedo Silva (2017)
The National Dengue Prevention and Control Program follows the health-care and campaign model since the 1920s. It was reaffirmed by the Plan for the Eradication of Aedes aegypti (PEAa) in the 1990s. The persistence in the use of this model can be pointed out as one of the causes that has caused an increasing of Dengue cases in recent years, with annual outbreaks in Brazil. The Ministry of Health, with a view to avoiding the occurrence of deaths, and with the goal of reducing property infestation to less than 1% in all municipalities, as well as the impact of the epidemics of Dengue in Brazil, created in 2009, the National Guidelines for Prevention and Control of Dengue Epidemics (DNPCED). The guidelines base on four components: Assistance, Epidemiological Surveillance, Vector Control, and Communication and Mobilization. This study aimed to evaluate the strategies of the National Dengue Control Plan and the annual epidemics of the disease in Uberlândia. The research methodological trajectory followed an ecological study, considering the spatial analysis of Dengue cases, Zika Virus and Chikungunya Fever occurred in Uberlândia from 2014 to 2016. Flaws found in the Vector Control that corroborate the high IIP (above 1%) of Aedes aegypti in the municipality, and the fact that more than 90% of these foci were found in places nearby houses, indicate that the goals were not met year after year, following the health care and campaign model with low or no participation of the residents. In order to solve this problem, the Territorialization of the Zoonoses Control Agents in Primary Care was introduced in the municipality, preferably in the zoning regime for the activities of the Zoonoses Control Agents, the Health Agents in Schools, and the Community Health Agents. Epidemiological Surveillance failures relate to disease reporting, incomplete or incorrect underreporting and reporting, delay in typing of notifications, and technical inability to perform spatial analysis of diseases. The alternative adopted by the municipality was the creation of the Health Observatory. Its main objectives are to support municipal management and to improve the services provided by the SUS to the population. The actions: development of technical reports and direct counseling to the Secretary of Health, and epidemiological bulletins to systematize and analyze the information contained in the Health Surveillance database. The flaws found in the assistance to patients affected by Aedes aegypti-transmitted diseases at times of outbreaks or epidemics in Uberlândia relate to the qualification of the management. It showed that the municipality presented lack of standardization of the medical conduct and many doubts in the differentiation of the diagnosis of Dengue, Zika and Chikungunya Fever. It was necessary to develop a program of Permanent Education to mark the information of these diseases and training by physicians from the Family Health Program and obstetricians from the municipal network, by the Municipal Health Department, in partnership with the Federal University of Uberlândia. Failure in communication and social mobilization base on sanitary campaigns practices, with emphasis on epidemic situations. In order to remedy this failure, the Municipal Health Secretary created the InterInstitutional Committee to organize actions involving the public and private sectors. This work proposes a reorganization of the components of the DNPCED. Mobilization and Communication divided among the other three components in a transversal-intersectoral form, not in a compartmentalized, way but through an articulated network of complementary services.